Two new deep-water species of Caecoserolis Wägele, 1994 (Isopoda, Sphaeromatidea,Serolidae) from off North Island, New Zealand - Bruce, Niel L. (Zootaxa, 2008)
Two species of Serolidae, Caecoserolis carinata sp. nov. and Caecoserolis bicolor sp. nov. are described from northern New Zealand waters, the first record of the genus from New Zealand. A third species, a juvenile is recorded as Caecoserolis sp. All are deep-water species. C. carinata can be identified by the median row of prominent tubercles, and was collected from the southern New Caledonia Trough, Tasman Sea at depths of 2930–3184 m; C. bicolor has paired nodules on the head linked by a V-shaped ridge, a broad body, widest at pereonites 3 and 4, and occurs off Hawkes Bay, off eastern North Island, at depths of 2119–2337 m.